Persepsi Klien Tentang Komunikasi Terapeutik Perawat Ditinjau dari Latar Belakang Pendidikan Perawat - Rahmat Pannyiwi; Nurhaedah Nurhaedah; Andi Hariati; Rezqiqah Aulia Rahmat (Jurnal Keperawatan Profesional (KEPO), 2021)
The therapeutic communication is aimed to change the clients' behavior in reaching an optimal awareness. This research aimed to obtain a client perception view about Nursery Therapeutic Communication in Intensive Surgery Care Unit at Hospital Sidenreng Rappang Regency. The kind of research is descriptive with purposive sampling according to inclusive criteria. The variables are verbal and in-verbal communications. Instrument to collect data is questionnaire, whereas the questionnaires are directly fulfilled by the respondents. From the analysis, the researcher found that the 63,5 % of respondents have a good perception toward nursery verbal therapeutic communication and the non-verbal the researcher found that the 85% of respondents have a good perception toward nursery non-verbal terapeutik. The result shows a great clients' perception about nursery therapeutic communications. As for the suggestion, Hospital Sidenreng Rappang Regency shall give a fresh knowledge or seminars to operasional nurses about nursery therapeutic communications in hospital scope.